Thyroid Storm in Post-Partum in Bangkalan Hospital: A Case Report - Lambu Henderika Dacosta; Ferdy Royland. Marpaung (Institute of Medico-legal Publications Pvt Ltd, 2021)
Thyroid crisis is a rare complication of hyperthyroidism, with a greater risk about 10 times during pregnancy,also clinical manifestations and significant increasing of level of thyroxine (T4) and tri-iodothyronine (T3).Thyroid crisis could cause mortality in >10%. A 58-year-old female was referred from Bangkalan Hospital,presented with palpitation, shortness of breath, diarrhea 2-3×/day, vaginal bleeding, fever for 1 day beforeadmittance. Hyperthyroid for 3 years ago and routinely consumed thyrozol (1×2tab) in 2 years but didnot take the medicine for 1 year ago. Physical examination: BP 147/100 mmHg, pulse rate 124×/minute,temperature 38.4 ºC, RR 30/minute, conjunctiva anemia, thyroid palpable, exopthalmus. ECG results:presence of sinus tachycardia, Chest X-Ray: cardiomegaly. Burch Wartofsky Score obtained a total scoreof 45, (temperature 38.5 C=15, diarrhea=10, tachycardia=15, CHF=5). Laboratory results: TSH <0.004 IU/mL, FT4 5.31 ng/dl. Thyroid crisis is a rare case of hyperthyroidism, a greater risk during pregnancy whichcould lead to death. Many symptoms arise in hyperthyroidism which could lead to thyroid crisis. The criteriawhich used to assess thyroid analysis is the Burch Wartofsky Score, FT4 levels increased 5.31 ng/dl. Thispatient was diagnosed as thyroid storm in post-partum, based on Burch Wartofsky Score, low TSH level andan elevated FT4 level and not taking medicine for 1 year ago.